Analytical construction of the hierarchical matrix Lyapunov function for impulse systems - Begmuratov, K. A.; Martynyuk, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For impulse systems, we develop a method for the construction of the hierarchical matrix Lyapunov ffunction.